Regenerasi dan Pertumbuhan Beberapa Varietas Tebu (Saccharum officinarum L.) secara In Vitro - Deden Sukmadjaja; Ade Mulyana (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2011)
(Saccharum officinarum L.) through In Vitro Culture.Deden Sukmadjaja and Ade Mulyana. The research wasconducted at the Laboratory of Tissue Culture The Biology ofCell and Tissue Researcher Group ICABIOGRAD, Bogor fromJune to November 2009 to studied growth and regenerationsresponse some varieties of sugarcane through in vitroculture. The research activities have been carried out inthree steps, i.e., callus formation, regeneration of shoots androots regeneration. The type of explants used in the studywas in vitro planlet explants of both sugarcane varieties.Seven media formulations were used for the callus inductionand regeneration of shoots, while five media formulationswere used for the roots regeneration. The resultsshowed that the highest respond for calluses induction wasBulu Lawang varieties at media formulation MS + 2.4-D 2mg.l-1 + BAP 0.4 mg.l-1 + CH 2000 mg.l-1 and PS 951 varietiesat media formulation MS + 2.4-D 1 mg.l-1 + BAP 0.4 mg.l-1.While the highest respond for regeneration of shoots wasBulu Lawang varieties at media formulation MS0 (controlMS) dan PS 951 varieties at media formulation MS + BAP 1mg.l-1 + kinetin 1 mg.l-1 + NAA 0.5 mg.l-1 + GA3 0.5 mg.l-1.The highest respond of roots regeneration was Bulu Lawangand PS 951 varieties at media formulation MS + IBA 1 mg.l-1.Acclimatization of plantlets produced were grew successfullyabout 90-100% in greenhouse.